An integrated process‐based model of flutes and tool marks in deep‐water environments: Implications for palaeohydraulics, the Bouma sequence and hybrid event beds. Issue 4 (11th May 2020) - Peakall, Jeff; Best, Jim; Baas, Jaco H.; Hodgson, David M.; Clare, Michael A.; Talling, Peter J.; Dorrell, Robert M.; Lee, David R.
Abstract: Flutes and tool marks are commonly observed sedimentary structures on the bases of sandstones in deep‐water successions. These sole structures are universally used as palaeocurrent indicators but, in sharp contrast to most sedimentary structures, they are not used in palaeohydraulic reconstructions or to aid prediction of the spatial distribution of sediments. Since Kuenen's famous 1953 paper, flutes and tool marks in deep‐water systems have been linked to turbidity currents, as reflected in the standard Bouma sequence taught to generations of geologists. Yet, these structures present a series of unaddressed enigmas. Detailed field studies in the 1960s and early 1970s observed that flutes are typically associated with thicker, more proximal beds, whilst tools are generally prevalent in thinner, more distal, beds. Additionally, flutes and tool marks are rarely observed on the same surfaces, and flutes are seen to change downstream from larger wider parabolic to smaller narrower spindle‐shaped forms. No model has been proposed that explains these field‐based observations. This contribution undertakes a radical re‐examination of the formative flow conditions of flutes and tool marks, and demonstrates that they are the products of a wide range of sediment gravity flows, from turbulent flows, through transitional clay‐rich flows, to debris flows. Flutes are not solely the product of turbulent flows, but can continue to form in transitional flows. Grooves are shown to be formed by debris flows, slumps and slides, not turbidity currents, and in many cases the debris flows are linked to the debritic component of hybrid flows. Discontinuous tool marks, including skim (bounce) marks, prod marks and skip marks, are shown to be formed by transitional mud‐rich flows. Consequently, the observed spatial distribution of flutes and tool marks can be explained by a progressive increase in flow cohesivity downstream. This model of flutes and tool marks dovetails with models of hybrid flows that predict such a longitudinal increase in flow cohesivity. However, some deposits show grooves preferentially associated with Bouma TA beds, and these are likely formed by flows transforming from higher to lower cohesion, and are present in basins where hybrid beds are absent or rare. The recognition that sole structures may have no genetic link to the later overlying turbidity current deposits, and can be formed by a wide range of flow types, indicates that the existing pictorial description of the Bouma sequence is incorrect . A modified Bouma sequence is proposed here that addresses these points. In utilizing the advances in fluid dynamics since Kuenen's pioneering research, this study demonstrates that it is possible to use flutes and tool marks to interpret flow type at the point of formation, the nature of flow transformations, and the mechanics of the basal layer. These advances suggest that it is then possible to predict the nature of deposit type down‐dip. This new understanding, in combination with further testing in outcrop of the proposed relationships between sole marks and palaeohydraulics, opens up a wealth of possibilities for improving the understanding of deep‐water clastic environments, with implications for developing more complete facies models, assessing subaqueous geohazards and the resilience of seafloor infrastructure, and advancing our understanding of deep‐water sediments as archives of palaeoenvironmental change.